Asesmen Kerusakan Bangunan Sekolah dan Penyusunan Rekomendasi Prioritas Perbaikan untuk Meningkatkan Keamanan dan Kenyamanan : Pengabdian - Budi Kurniawan; Muhammad Azhar; Muhammad Chairi Munajar; Nurul Fajariah; Alfa Della (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The community service activity was carried out to assist SMPS Waladun Sholeh in conducting an inspection of school building conditions, specifically regarding structural, architectural, and utility elements, which have posed challenges due to limited technical expertise within the school. The inspection plays an important role since school buildings are fundamental to maintaining the continuity of the teaching–learning process. The method employed was on-site inspection, including visual observation, measurements, inventorying building elements, and quantitative analysis of damage levels. In addition, interviews were conducted with school representatives to obtain supporting information regarding the history of damage and maintenance. The activity stages included: (a) initial coordination and collection of basic building data; (b) field inspection of structural, architectural, and utility components; (c) analysis of damage levels and determination of the building condition category; and (d) dissemination of inspection results and proposed follow-up plans to the school. The results indicate that most building components remain in good condition, with minor damage predominating and accounting for 13.40% of the total elements inspected. However, an uneven settlement of the foundation was detected, causing cracks and deformations in several parts of the building.